Online Medical Education for Doctors: Identifying Potential Gaps to the Traditional, Face-to-Face Modality. (February 2019) - Ifediora, Chris O
Background: Online education options increasingly complement traditional face-to-face (F2F) approaches. Few studies have compared both formats on doctors, and little evidence exists to prove that the online approach is universally effective. This gap needs to be addressed to ensure that the quality of education and health care delivery is not compromised. Methods: A quantitative survey targeting 881 doctors that required online and F2F teaching sessions offers identical contents over a 12-month period. The surveyed doctors work in the Australian after-hours house-call (AHHC) industry, and the teachings were parts of their continuing professional development activities. Results: In all, 89 responses were received; 10 (11.2%) participated exclusively online, while 23 (25.8%) did so by F2F; 52 (58.4%) engaged through both modalities. No statistical differences existed based on sex, specialty, and post-graduate fellowship status, as well as on the perceptions with teaching structure, contents, and duration of the education programmes. However, F2F-only doctors were likely to be junior and younger than 40 years (odds ratio [OR]: 3.85; P = .01). They also admit easy access to effective teaching environment (OR: 4.07; P = .01) and receive better feedbacks (OR: 3.75; P = .01). Conversely, online-only participants were more likely to combine AHHC duties with regular-hours general practice (OR: 0.15; P = .02) and are generally more satisfied with the programme frequency (OR: 6.90; P = .01). Conclusions: On multiple areas, no differences exist in the medical education delivered by online and the F2F methods to doctors and both should be encouraged. However, younger and junior practitioners, who tend to need feedbacks on their jobs, should participate more in the F2F sessions.